Pembuatan Bahan Ajar Digital Akuntansi Keuangan di SMA Islam Nabilah - Santi Yopie; Sania Apri Yanti (Universitas Internasional Batam, 2021)
The COVID-19 pandemic that hit Indonesia prompted the Indonesian government to issue a new policy to carry out teaching and learning activities online. This new policy of online teaching and learning activities has brought many difficulties, especially for students whose learning media is less attractive and difficult to understand. The making of digital teaching materials is aimed at Nabilah Islamic High School with the aim of this activity the writer wants to help schools in digital learning media for teaching and learning activities, and makes it easier for students to understand service company financial accounting lessons. The learning media made are in the form of learning modules, power points, and animation videos. Data collected by interview techniques, observation, and literature study. The results of making digital teaching materials are implementing the outputs that have been made to students by presenting them in class through online meetings. The hope of the writer is that the output produced can be used in the learning process in a sustainable manner.